Intervention programmes for HIV and AIDS prevention: a study of in- school adolescents in Orlu Senatorial Zone of Imo State, Nigeria - C., Ezeama M.; E., Enwereji E.; A., Onyekwere I. (International Journal of Advances in Medicine, 2017)
Background: Helpful strategies to prevent human immuno-deficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) among adolescents remain the greatest challenge in developing countries including Nigeria. In Nigeria, interventions for preventing HIV and AIDS for in-school adolescents are limited. This study used class-room instruction (CI) and drama (DR) for HIV and AIDS prevention among in-school adolescents in Orlu Senatorial Zone. Methods: A quasi-experimental design using 165 students from three randomly selected co-educational secondary schools was adopted. Two experimental groups (CI and DR) and a control group were used for the study. Baseline data were collected using a semi-structured questionnaire with 29-point knowledge and 9-point attitudinal scales. Knowledge was analysed using the scores <15 and ≥15 for low and high knowledge respectively. For attitude, scores of <5 and ≥5 were categorised as negative and positive respectively. The results for baseline studies were used to design interventions that were implemented for 8 weeks. Also, mid-term and follow-up evaluations were conducted during the study. Data were analysed using descriptive statistics, t-test and ANOVA at p=0.05. Results: The mean ages of the respondents in CI, DR and control groups were 13.4±1.2, 13.9±1.5 and 13.8±1.2 years respectively. Knowledge scores on HIV and AIDS at baseline were 20.5±2.7, 20.4±2.6 and 21.1±2.7 for CI, DR and Control groups respectively. These scores increased to 22.7±2.7, 22.6±1.8 and 21.2±0.3 at mid-term for CI, DR and control, respectively. At follow-up, scores for CI and DR increased to 23.9±1.8 and 24.5±1.4 respectively while the score for the control dropped to 20.0±2.8. Scores for attitude for CI, DR and control groups during baseline study were 5.3±1.4, 4.9±1.5 and 5.3±1.0 respectively. For mid-term, attitude scores were 5.1±1.2, 5.0±0.9 and 4.7±1.5 for CI, DR and control respectively while scores for follow-up were 5.3±1.2, 5.6±0.7 and 4.5±1.2, indicating greater increase among the intervention groups than that of control. Conclusions: Based on the results of the study, drama yielded more positive outcomes in both knowledge gained and in attitudinal change among in-school adolescents than classroom instruction. Drama intervention is therefore, an important HIV and AIDS prevention strategy for in- school adolescents.